2007
DOI: 10.1002/esp.1489
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial thermal erosion: heat balance integral method

Abstract: In periglacial regions, frozen river banks are affected by thermal and mechanical erosion. In Siberia, bank retreats of up to 40 m per year are observed. This thermal erosion occurs during a few weeks, at springtime, for high enough water temperatures and river discharges. Until now, models of thermal erosion have been based on the assumption of a constant thermal erosion rate. We have developed a more general model at variable rate, whose solution is calculated using the integral method. Results of this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 12 publications
1
41
1
Order By: Relevance
“…The dependence of e on θ w is found from considering Fig. 4 of Randriamazaoro et al (2007), and their discussion, as well as the results of a constantrate melting model (Costard et al, 2003), which together imply that e is proportional to θ w . Finally, after studying the bottom-left graph of Fig.…”
Section: Bed Erosion Ratementioning
confidence: 65%
See 2 more Smart Citations
“…The dependence of e on θ w is found from considering Fig. 4 of Randriamazaoro et al (2007), and their discussion, as well as the results of a constantrate melting model (Costard et al, 2003), which together imply that e is proportional to θ w . Finally, after studying the bottom-left graph of Fig.…”
Section: Bed Erosion Ratementioning
confidence: 65%
“…the erosion of the cryosphere that forms the bedrock by disaggregation of silicates as interstitial ice is melted. We have modified a treatment of thermal erosion of the frozen banks of periglacial rivers on Earth (Randriamazaoro et al, 2007) for application to Mars, where the ground temperature is much less, using the following analysis. The primary controlling parameters of the erosion rate, e, are the Reynolds number, Re, and the water temperature, θ w .…”
Section: Bed Erosion Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The observations of coastal erosion of the Lena River and measurement of the water temperature allowed establishing a direct dependency for the increase of the volume of the deformations caused by thermoerosion on the increasing temperature of the water during the flood (Coastard et al 2007, Dupeyrat et al 2011. Simulation of this dependency in the work of Randriamazaoro et al (2007) showed that the erosion rate can increase by an average of 20% with an increase of the water temperature by 2°C. These results were used to test the model presented Fig.…”
Section: Validation Of the Model And Resultsmentioning
confidence: 99%
“…This structure of the banks makes the abrasion processes even more pronounced (Dallimore, et al 1996, Coastard et al 2007, Bowden 2010. The laboratory experiments and field observations (Randriamazaoro et al 2007, Dupeyrat et al 2011 showed that thermoerosion plays a significant role in the deformation of the banks composed of permafrost with the inclusion of layers of ice. Sometimes the effect of thermoerosion is greater than that of mechanical erosion.…”
Section: Introductionmentioning
confidence: 99%